Content validity of an innovative behavior rubric for polytechnic engineering students - Che Derasid, Nor Aisyah; Musta’amal @ Jamal, Aede Hatib; Suhairom, Nornazira; Suswanto, Hary (Institute of Advanced Engineering and Science, 2025)
In engineering education, fostering innovative behaviors is crucial for preparing students to tackle complex, real-world challenges. Developing an assessment tool or rubric that accurately measures innovative behavior is essential to provide educators with the means to systematically evaluate students’ innovative potential. This article mainly focuses on assessing the content validity of the innovative behavior assessment rubric, which is designed to measure the innovative behavior of engineering students. The rubric was designed around three core dimensions: problem recognition, idea generation, and idea implementation. Content validity was assessed using the item-level content validity index (I-CVI), scale-level content validity index (S-CVI), and modified kappa statistic. Expert evaluations resulted in a final 35-item rubric, with an overall S-CVI of 0.85, indicating high content validity. Items with I-CVI values below 0.70 were either revised or removed to ensure relevance and clarity. The study highlights the importance of expert judgment in the validation process and underscores the utility of both I-CVI and kappa in refining assessment tools. Future research will focus on construct and criterion validation, as well as practical application across diverse educational contexts.